Cytotoxic activity of Ferula persica gum essential oil on murine colon carcinoma (CT26) and Vero cell lines. Issue 2 (3rd March 2020) - Hosseinzadeh, Neda; Shomali, Tahoora; Hosseinzadeh, Saeid; Raouf Fard, Fatemeh; Jalaei, Jafar; Fazeli, Mehdi
ABSTRACT: In this study, murine colon carcinoma (CT26) as well as non-cancerous Vero cells were exposed to various concentrations of essential oil (EO) obtained from the gum of F. persica (0.125 × 10 −9 to 20 µl/ml and 0.125 × 10 −9 to 80 µl/ml, respectively) for 24 h. The cytotoxicity and apoptosis were determined using MTT assay and acridine orange/ethidium bromide (AO/EB) staining, respectively. Clonogenic assay was also performed. Among 28 compounds that were determined by GC/MS, the major constituent of the EO was α-pinene (27.1%). A dose-dependent cytotoxicity was observed on CT26 cells with IC50 value of 0.0010 µl/ml. The cytotoxicity on Vero cells was relatively low with IC50 value of 0.3247µl/ml. The EO induced apoptosis in both cells and colony formation was also inhibited. In conclusion, the EO obtained from the gum of F. persica has cytotoxic and apoptotic effects on CT26 cell line with lesser effects on Vero cells.